Students' perspectives of an EAP pathway program - Dooey, Patricia (Elsevier, 2010)
Increasing numbers of overseas students are applying to study at universities in Australia. Many students who meet all of the university's academic entry requirements except English language proficiency are offered pathway programs which prepare them for their tertiary studies. To date, much of the research relating to international students focuses on their progress in tertiary, rather than pathway programs, and little is known about the students' own impressions. One such program in Western Australia was the subject of a two-phase study which was carried out through interviews with thirteen students from a range of cultural and linguistic backgrounds, in order to find out what perceptions they had of its effectiveness. The participants noted that they had benefited from taking this program, as it had provided them with a good transition to studying in Australia, but a number of obstacles still had to be overcome. The results also reveal that readiness to study in a tertiary institution goes well beyond the achievement of an English language proficiency score for entry. Modifications to the program are recommended.